Impact of Visual Learning Environment (VLE): a case study on students’ academic performance by subject / M. Y. Mohd Yusop ... [et al.] - M. Y., Mohd Yusop; M. N., Mansor; M. K., Ramli; F. I., Abd Samad; K. A, Mat Saad; S. E., Abdul Hamid; Z. Z., Mukhtar (UiTM Press, 2018)
Education in the 21st century has created demands for new tools to better accommodate the teaching and learning processes at various levels of education; all with the objective of improving the understanding of students and as such, will be reflected through improved academic performances. This in turn creates opportunity to study the impact of such modern learning platforms on the academic performances of students as a group or as an individual. The magnitude of such impact also varies depending on the types of subjects. In this study, the comparison is done between technical and non-technical based courses. Sampling conditions were also identified so as to ensure a fair treatment of data used in the analysis. Factors such as whether a particular subject is being taught by the same lecturer across a period of three consecutive semesters and the number of activities done in a Visual Learning Environment (VLE) for a particular subject as were taken into consideration. Results of the analysis were presented graphically where trending attributes were highlighted and discussed. Suggestions to improve the study, to increase the positive effects of VLE activities on the overall academic performances of students as well as the proposed initiatives that can be taken to increase the number activities in a subject’s VLE were also elaborated in the paper.